The influence of social media marketing on the rise of emerging African Language repertoires in South African digital communication - Mokgesi-Selinga, Masabata (Graduate School of Business (GSB), 2025)
The multilingual South African landscape is represented by the country's twelve official languages, of which nine are African languages. This landscape presents an opportunity for brands to foster inclusive communication with and amongst diverse communities. As global communication increasingly becomes digitalised, social media is rapidly growing as an easily accessible communication platform for social engagements and digital marketing. This study aimed to analyse how African language speakers communicate with and about local brands on social media platforms to identify emerging social media trends and marketing opportunities using African languages when engaging with South African consumers. The research case study primarily observed the interaction between four proudly South African brands and the brands' “followers” on three social media platforms. The four brands were selected for being top-performing African brands that play a significant role in driving the continent's economic growth. The said brands have also enhanced their digital communication, resulting in stronger consumer engagement. The qualitative data was collected through screenshots of social media posts by the brands and their followers. For data integrity and analysis, the screenshots were converted into verbatim texts. Core findings indicate that social media platforms, particularly Twitter—rebranded as “X” —, are the quickest way to initiate and broadcast new African language repertoires. The social media platforms of four brands were included in this study: two food brands and two financial brands. The chicken-based food outlets, Nando's SA and Chicken Licken SA, went out of their way to celebrate the linguistic, cultural and social diversity of their followers by embracing new language repertoires, code-switching, and interacting with a great sense of humour. Meanwhile, the financial brands, Capitec and OUTsurance, did not communicate with followers in African languages, and their shortcoming was that they forfeited broader consumer engagement. This study illustrated that brands that engage consumers with familiar social jargon, such as emerging African language repertoires, have the potential to maximise their marketing opportunities, as observed from the social media marketing of Chicken Licken SA and Nando's SA.